Achieving sustainable development in China: a moderated mediation model of guanxi HRM practices - Zhang, Xueqin; Wang, Zerui; Lee, Junho; Xu, Fei (Frontiers in Psychology, 2025)
IntroductionCurrently, few studies have examined the negative effects of human resource management (HRM) practices on employees’ voice behavior and turnover intention. This study aims to explore the underlying mechanisms and boundary conditions by which guanxi HRM practices influence employees’ turnover intention and voice behavior in the Chinese context, drawing on the conservation of resources theory.MethodsUsing a three-wave survey of 243 employees, we analyzed a moderated mediation model.ResultsThe results revealed that guanxi HRM practices were positively associated with turnover intention and negatively associated with voice behavior, with job meaningfulness serving as a mediator in these relationships. Furthermore, we found that ethical leadership mitigated the negative relationship between guanxi HRM practices and job meaningfulness, as well as the indirect effects of guanxi HRM practices on turnover intention and voice behavior through job meaningfulness.DiscussionThese findings deepen our understanding of the interaction between guanxi HRM practices and ethical leadership, as well as their combined effects on job meaningfulness, turnover intention, and voice behavior, and provide practical implications for organizations and managers.